Isolation and preliminary characterization of gas1-1, a mutation causing partial suppression of the phenotype conferred by the gibberellin-insensitive (gai) mutation in Arabidopsis thaliana (L.) Heyhn. - Carol, P; Peng, J; Harberd, N (1995)
The semi-dominant gai mutation of arabidopsis confers a dark-green dwarf phenotype resembling that of gibberellin (GA)-deficient mutants. In contrast to GA-deficient mutants, gai mutants do not respond to GA treatments and accumulate higher levels of bioactive GAs than are found in wild-type controls. The gai mutation thus alters the responses of plant cells to GA, indicating that the GAI (wild-type) gene product is involved in GA reception and/or signal transduction. Here we describe the isolation and preliminary characterization of a mutation, gas1-1, which is not linked to gai and which partially suppresses the effect of the gai mutation. Double mutant, gai gas1-1, homozygotes are less severely dwarfed and lighter green than gai GAS1 controls. However, comparisons of the effects of treatments with exogenous GA demonstrate that gas1-1 does not increase the GA responsiveness of the gai mutant. Thus the gas1-1 mutation appears to reduce the GA-dependency of plant growth, and identifies a gene (GAS1) whose product is a candidate GA signal-transduction component.